Computational simulations of the human magneto− and electroenterogram - Lin, A; Buist, M; Cheng, L; Smith, N; Pullan, A (2006)
Many functional pathologies of the small intestine are difficult to diagnose clinically without an invasive surgical intervention. Often such conditions are associated with a disruption of the normal electrical activity occurring within the musculature of the small intestine. The far field electrical signals on the torso surface arising from the electrical activity within the small intestine cannot be reliably measured. However, it has been shown that abnormal electrical activity in the small intestine can be distinguished by recording the magnetic fields of intestinal origin immediately outside the torso surface. We have developed an anatomically-based computational model to simulate slow wave propagation in the small intestine, the resulting cutaneous electrical field and the magnetic field outside the torso. Using both a one-dimensional and a three-dimensional model of the duodenum we investigate the degree of detail that is required to realistically simulate this far field activity. Our results indicate that some of the qualitative behavior in the far field activity can be replicated using a one-dimensional model, although there are clear situations where the greater level modeling detail is required.